Respuesta :

Answer:

no solution.

Step-by-step explanation:

The given equation is

[tex]\sqrt{b-17}+\sqrt{b}=1[/tex]

[tex]\mathrm{Subtract\:}\sqrt{b}\mathrm{\:from\:both\:sides}\\\sqrt{b-17}+\sqrt{b}-\sqrt{b}=1-\sqrt{b}[/tex]

On simplifying, we get

[tex]\sqrt{b-17}=1-\sqrt{b}[/tex]

Squaring both sides

[tex]\left(\sqrt{b-17}\right)^2=\left(1-\sqrt{b}\right)^2\\\\b-17=1-2\sqrt{b}+b[/tex]

Subtract b from both sides

[tex]17=1-2\sqrt{b}[/tex]

On simplifying, we get

[tex]-18=-2\sqrt{b}[/tex]

Squaring both sides

[tex]324=4b\\\\b=81[/tex]

Now, we substitute this value in the original equation

[tex]\sqrt{81-17}+\sqrt{81}=1\\\\\sqrt{64}+9=1\\\\8+9=1\\\\17=1\text{ This is False}[/tex]

Hence, b = 81 is an extraneous solution.

Therefore, the given equation has no solution.

Answer:

no solution

Step-by-step explanation:

person above me was right :)